Autonomous Systems 2019: An Almanac - Unger, Herwig (VDI Verlag, 2019)
Since 2010 it became a good tradition that colleagues from different research areas publish articles about their unsolved scientific problems, on-going work or research results in a joint book with the title “Autonomous Systems”. Those systems exist in several areas of science, describing self-contained and self-controlled groups of possibly interacting or interrelated entities that form unified ensembles acting in given environment without outer control of any higher instances, leaders or managers. In this year, three major topics are presented, which are valiant, strongly interfering with politics and everyone’s discussion and are, therefore, rarely considered without emotions or political and financial concerns: the climate on our planet earth, ethics in the context of applying and using autonomous systems as well as problems of (mostly individual) road traffic. The following contributions deal with various topics related to theory, fundamentals, natural language and image pro...